Neurofibromatosis type 2 misdiagnosed as amblyopia—a case report and literature review - Li, Qian; Liu, Guiqin (Frontiers in Medicine, 2025)
Neurofibromatosis type 2 (NF2) is characterized by bilateral vestibular schwannomas, and approximately 40–70% of affected children show ophthalmological involvement. Ophthalmological features may be the first sign of NF2; however, the symptoms associated with ocular lesions are diverse. The onset of NF2 is often obscure, resulting in missed or misdiagnosed cases. Herein, we report a case of NF2 in a child who initially presented with poor eyesight. The child had been treated for amblyopia for 7 years and was referred to the eye oncology department due to a lack of improvement in vision. At birth, a soft mass was noted scattered across the abdominal skin and scalp, which gradually increased in size over time. Ophthalmological examination revealed posterior subcapsular opacity in the right eye and an anterior retinal hamartoma in the left eye. Orbital and cranial magnetic resonance imaging (MRI) indicated that the T1 and T2 signals of multiple structures, including the cone, auditory nerve, trigeminal nerve, left oculomotor nerve, paravertebral, and sublingual region, were more uniform after enhancement. A genetic heterozygous mutation was detected, with no family history of the condition. In addition to this case, we collected and summarized 158 publicly reported cases of NF2 with ophthalmological characteristics. Among these cases, the incidence of visual impairment, strabismus, cataract, retinal anomaly, and retinal hamartoma was high, reaching 64, 38, 25, 23, and 16%, respectively. Through analysis and discussion of the clinical and imaging characteristics of NF2 ocular lesions, we aim to improve ophthalmologists’ understanding of this disease, thereby reducing the rate of missed diagnoses.